Диверсифікація джерел інклюзивного інвестування аграрних бізнес суб'єктів - Степаненко, С. В. (My University, 2023)
Розв’язання життєво важливих для України завдань сталого розвитку та забезпечен-ня стратегічної конкурентоспроможності вітчизняного агросектору вимагають опрацювання нетрадиційних підходів до пошуку механізмів і джерел інвестування галузі і сільських територій. Чисельні проблемі аспекти, з якими стикається агросектор протягом останніх років, поглиблюються та загострюються наявністю військового конфлікту у країні. За таких реалій аспекти обґрунтування джерел інвестиційного забезпечення постають домінантним елементом механізму господарювання. Стаття присвячена дослідженню фактичної структури джерел інвестування бізнес-суб’єктів агросектору України та пошуку перспективних напрямів їх удосконалення. Аналіз показав, що основним джерелом фінансування інвестицій аграрних формувань, традиційно, залишається власний капітал. Це значно звужує масштаб інвестиційного потенціалу агросфери, розширення якого має відбуватись у напрямі інклюзивних трансформацій галузі і сільських територій. У зв’язку з цим у статті обґрунтовано ландшафт рамкової національної політики інклюзивного інвестування агробізнесу і сільських територій. Запропоновано ключові принципи інклюзивного інвестування агробізнес-структур. Досліджено окремі сучасні реалії зарубіжної практики інклюзивного інвестування, на засадах якої обґрунтовано напрями диверсифікації джерел інвестиційного забезпечення діяльності українських агрокомпаній. В основу методичного підходу до обґрунтування запропоновано покласти баланс інтересів всіх учасників агросуспільного процесу, інструментарій управління ризиками інклюзивного агроінвестування, принципи змішаного фінансування та процеси цифровізації. Результати досліджень можуть бути використані аграрним бізнес-структурами, які віддані пріоритетам сталого розвитку у своїй корпоративній культурі управління. It is necessary to solve the tasks of sustainable development that are vital for Ukraine and ensure the strategic competitiveness of the domestic agricultural sector today. This requires developing non-traditional approaches to finding mechanisms and sources of investment in the industry and rural areas. The numerous problematic aspects faced by the agricultural sector in recent years are deepened and exacerbated by a military conflict. Under such realities, parts of substantiation of sources of investment support become a dominant element of the management mechanism. The article is devoted to studying the structure of investment sources of business entities in the agricultural sector of Ukraine and searching for promising directions for their improvement. Own capital remains the primary source of financing investments in agrarian formations. This significantly narrows the scale of the investment potential of the agricultural sector, the expansion of which should take place in the direction of inclusive transformations of the industry and rural areas. The landscape of the framework national policy of inclusive investment of agribusiness and rural areas is substantiated in the article. The fundamental principles of inclusive investment in agribusiness structures are proposed here. Separate modern realities of the foreign practice of inclusive investment are investigated based on which the directions of diversification of the sources of investment support for the activity of Ukrainian agricultural companies are substantiated. The balance of interests of all participants in the agro-social process, risk management tools of inclusive agro-investment, principles of mixed financing, and digitalization processes are the basis of the author's systematic approach. Mixed financing and social responsibility of agricultural businesses should become the economic basis for differentiating sources of inclusive investment of agricultural business entities. Research results can be used by agricultural business structures committed to sustainable development priorities in their corporate management culture.
Diversification of sources of inclusive investment of agricultural business subjects
Keywords: сільське господарство; сільські території; агроінвестиції; нклюзивність; сталий розвиток; інвестиційна привабливість; agriculture; rural areas; agricultural investments; inclusiveness; sustainable developmen; investment attractiveness